Residential and stock market effects on consumption across Europe. - Pacheco, Luís Miguel (2014)
The aim of this paper is to explain private consumption as a function of income and wealth with data from European Union countries. To examine how the developments in housing and stock markets may have affected consumption behaviour, we adopt two econo- metric procedures. First, we use the Stock–Watson procedure to account for wealth effects on consumption over the long run. Second, through an error-correction model we measure wealth effects on consumption over the short run. We found signiﬁcant albeit mixed values for the long-run elasticities of consumption with respect to real residential and equity prices. We also found strong evidence that consumption exhibits error-correction behaviour in the short run, with the value of the error-correction term signifying that household consumption takes several quarters to completely respond to changes in the markets.